Will in-flight virtual reality increase the enjoyment of flight for anxious passengers? - Hibar Syahrul Gafur; Hasrini Sari; Titah Yudhistira (Cogent Business & Management, 2023)
This study explores the possibility of using VR as an in-flight entertainment tool. The relationship between flight-related anxiety and attitude toward using in-flight VR is examined. Furthermore, the willingness to buy airline tickets is also explored if in-flight VR entertainment is provided. The primary research model refers to the Virtual Reality Hardware Acceptance model. Flight-related anxiety variables and covariates are used as the antecedents of attitude toward using in-flight VR. In addition, the intention to buy airline tickets is also measured as the dependent variable to explore the influence of attitude toward using in-flight VR. The method of data collection is accomplished purposively by an online survey. Hypotheses testing is done using PLS-SEM. The bootstrap-based multi-group analysis (MGA) is taken to distinguish the significance level between two data groups: high and low anxiety. Perceived enjoyment is the main predictor that significantly affects the passenger's attitude toward using in-flight VR for passengers with a high level of anxiety. However, price willingness to pay does not influence perceived enjoyment. Attitude toward using in-flight VR influences both groups' intention to buy airline tickets. The originality of the research:Instead of using VR as a therapy tool, this study explores the possibility of using it as an in-flight entertainment tool for anxious passengers.
Keywords: 650; acceptance model; airlines; attitude toward in-flight VR; enjoyment; intention to buy tickets; Virtual reality